Catheter-related Complications and Potential Risk Factors Among Catheterized Cancer Patients Receiving Parenteral Nutrition at The University of Texas MD Anderson Cancer Center: A 26, 000 Parenteral Nutrition-day Experience. (4th October 2017) - Reitzel, Ruth; Chaftari, Anne-Marie; Feldman, Adina; Numan, Laith; Hachem, Ray Y; Rosenblatt, Joel; Raad, Issam
Abstract: Background: Parenteral nutrition (PN) is used as nutritional support in patients that are malnourished, critically ill, and/or have a nonfunctional gut. Patients receiving PN are at increased risk for both infectious and noninfectious catheter complications often leading to increased morbidity and mortality. Risk factors for catheter complications in patients receiving PN are often variable and poorly understood. Methods: We conducted retrospective study among cancer patients who received PN between January 1, 2013 and December 31, 2015 at the University of Texas MD Anderson Cancer Center. Rate and prevalence of central line associated blood stream infection (CLABSI) and noninfectious catheter complications were assessed. Additionally, prevalence and time-to-infection of causative pathogens were evaluated. Multivariate logistic regression analyses were conducted in a sample of the PN population to identify risk factors for both infectious and noninfectious catheter complications. Results: We identified 46 CLABSI cases in 38 patients of the 1, 762 patients receiving PN (1.73 episodes of CLABSI per 1000 PN days). Gram-positives (37.84%) and yeast (29.73%) were the most common pathogens, with catheter-related Candidemias occurring earlier than gram-positive or gram-negative CLABSI. Noninfectious catheter complications occurred in 56 patients (38.6%). Multivariate analysis identified age, GVHD, and history of occlusion in the same catheter, as well as intestinal failure and long-term PN use as significant risk factors for CLABSI and noninfectious catheter complications, respectively. Conclusion: Patients receiving PN are at higher risk for both infectious and noninfectious catheter complications. Compared with national averages of CLABSI, the prevalence of catheter-related Candidemias in the PN cancer patient population was increased. This study highlights the need for development of more effective targeted preventative interventions. Disclosures: J. Rosenblatt, Infective Technologies, LLC: Co-Inventor of the Nitroglycerin-Citrate-Ethanol catheter lock solution technology which is owned by the University of Texas MD Anderson Cancer Center (UTMDACC) and has been licensed by Novel Anti-Infective Technologies, LLC in which Dr. Rosenblatt is a and Shareholder, Licensing agreement or royalty; UT MD Anderson Cancer Center: Co-Inventor of the Nitroglycerin-Citrate-Ethanol catheter lock solution technology which is owned by the University of Texas MD Anderson Cancer Center (UTMDACC) and has been licensed by Novel Anti-Infective Technologies, LLC in which Dr. Rosenblatt is a s and Scientific Advisor, Licensing agreement or royalty; I. Raad, Merck: Grant Investigator, Research grant; Allergan: Grant Investigator, Research grant; Infective Technologies, LLC: Co-Inventor of the Nitroglycerin-Citrate-Ethanol catheter lock solution technology which is owned by the University of Texas MD Anderson Cancer Center (UTMDACC) and has been licensed by Novel Anti-Infective Technologies, LLC in which Dr. Raad is a s and Shareholder, Licensing agreement or royalty.